Modified quality of seasoning syrup for coating and enhancing properties of a food model using xanthan gum - Tunnarut, Duenchay; Pongsawatmanit, Rungnaphar (Agriculture and Natural Resources, 2018)
In the food industry, the quantity of seasoning syrup coating on the food surface plays an essential role in determining final product quality. The effect was investigated of xanthan gum (Xan; 0%, 0.1%, and 0.2%) on the rheological properties of seasoning syrups (35% and 45% sucrose) at different temperatures (25 °C, 35 °C, 45 °C, and 55 °C). The syrups containing Xan exhibited shear-thinning behavior (n< 1). The syrup viscosity increased with increasing Xan and sucrose concentrations but decreased with temperature. A regression model was developed for predicting syrup viscosity from Xan, sucrose, and temperature and showed good predictability. A dried, thin-sheet squid sample was used as a snack model for syrup coating. The syrup pickup increased as a function of the viscosity and approach plateau after 300% pickup. Xan enhanced the amount of syrup coating and total soluble solids (p < 0.05) but the water activity and moisture content values did not differ significantly (p > 0.05) among the samples with and without Xan. The results indicated that Xan could be used in the food industry to enhance the quality of syrup in terms of the viscosity for syrup pickup and the final quality of the product.